Changes in cellular local immunity of the cervix in patients with cervical intraepithelial neoplasia on the basis of endocervicosis - Selskyy, P. R. (Journal of Education, Health and Sport, 2015)
Selskyy P. R. Изменения клеточного звена местного иммунитета шейки матки у больных с цервикальной интраэпителиальной неоплазией на фоне эндоцервикоза = Changes in cellular local immunity of the cervix in patients with cervical intraepithelial neoplasia on the basis of endocervicosis. Journal of Education, Health and Sport. 2015;5(9):685-693. ISSN 2391-8306. DOIhttp://dx.doi.org/10.5281/zenodo.32168 http://ojs.ukw.edu.pl/index.php/johs/article/view/2015%3B5%289%29%3A685-693 https://pbn.nauka.gov.pl/works/657207 Formerly Journal of Health Sciences. ISSN 1429-9623 / 2300-665X. Archives 2011–2014http://journal.rsw.edu.pl/index.php/JHS/issue/archive Deklaracja. Specyfika i zawartość merytoryczna czasopisma nie ulega zmianie. Zgodnie z informacją MNiSW z dnia 2 czerwca 2014 r., że w roku 2014 nie będzie przeprowadzana ocena czasopism naukowych; czasopismo o zmienionym tytule otrzymuje tyle samo punktów co na wykazie czasopism naukowych z dnia 31 grudnia 2014 r. The journal has had 5 points in Ministry of Science and Higher Education of Poland parametric evaluation. Part B item 1089. (31.12.2014). © The Author (s) 2015; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland and Radom University in Radom, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/3.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 02.08.2015. Revised 05.09.2015. Accepted: 29.09.2015. Изменения клеточного звена местного иммунитета шейки матки у больных с цервикальной интраэпителиальной неоплазией на фоне эндоцервикоза Changes in cellular local immunity of the cervix in patients with cervical intraepithelial neoplasia on the basis of endocervicosis П. Р. Сельський P. R. Selskyy Государственное высшее учебное заведение “Тернопольский государственный медицинский университет имени И.Я. Горбачевского МОЗ Украины”, Тернополь, Украина State higher education establishment “Ternopil State Medical University by I. Ya. Horbachevsky of Ministry of Public Health of Ukraine” Summary Histological and immunomorphological investigation of 91 patients on endocervicosis and 11 patients on CIN is are carried out. The analysis of cellular circuid of immunity was taken with the help of monoclone antibodies to antigens lymphocytes CD3, CD4, CD8 and CD19. Majority of the patients with endocervicosis the infringement T-cellular of circuid immunity was observed. The density of the cellular infiltrate, including CD3-lymphocytes in the stroma of the cervix by endocervicosis with CIN did not differ from similar indicators by endocervicosis with no signs of dysplasia. The change in the proliferative activity of the epithelium in the area of dysplasia was revealed. On the basis of investigations we can make the conclusion about essential influence of the violation of the regeneration in conjunction with the immunity factors on endocervicosis progress. Keywords: endocervicosis, cervical intraepithelial neoplasia, cellular immunity, cellular infiltration Резюме Проведено гистологическое, морфометрическое и иммуноморфологическое исследование 91 больной с эндоцервикозом и 11 больных с цервикальной интраэпителиальной неоплазией (CIN). Анализ клеточного звена иммунитета проводился с помощью моноклональных антител к антигенам лимфоцитов CD3, CD4, CD8 и CD19. У большинства пациенток с эндоцервикозом наблюдалось нарушение Т-клеточного звена иммунитета. Плотность клеточного инфильтрата, в том числе CD3-лимфоцитов, в строме шейки матки при эндоцервикозе, совмещенном с СIN, не отличалась от аналогичных показателей при эндоцервикозе без признаков дисплазии. Выявлено существенное изменение пролиферативной активности эпителия в области дисплазии. На основе проведенных исследований можно сделать вывод о существенном влиянии нарушения регенерации в сочетании с местными иммунными факторами на прогрессирование данного заболевания. Ключевые слова: эндоцервикоз, цервикальная интраэпителиальная неоплазия, клеточный иммунитет, клеточный инфильтрат.